Mathematical modeling to optimize the allocation of referees in a soccer championship in Espírito Santo - Santos, Matheus Augusto Delunardo dos; Servare Junior, Marcos Wagner Jesus (Brazilian Journal of Production Engineering, 2021)
This work used the Operational Research in the Capixaba soccer Championship of series B of 2020 to implement a model that optimizes the allocation of referees and contributes to the reduction of current costs regarding their transport, through a solution that reduces the total distance traveled by referees to carry out the matches. Through Linear Programming, the solution presented would save 55% of the total distance covered originally and its expenses, in addition to the possibility of reducing costs with arbitrators who become idle. The exposed model can still be modified according to new restrictions, such as the obligation for all referees to be assigned to the games and to be applied in other sports.